Fabrication of Barium‐ and Strontium‐Doped Silica/Titania Hollow Nanoparticles and Their Synergetic Effects on Promoting Neuronal Differentiation by Activating ERK and p38 Pathways. Issue 7 (21st February 2014) - Kim, Sojin; Jang, Yoonsun; Oh, Wan‐Kyu; Kim, Chanhoi; Jang, Jyongsik
<x xml:space="preserve">Abstract</x> Pristine, barium‐doped, and strontium‐doped hollow nanoparticles (p‐HNPs, Ba‐HNP, and Sr‐HNP; HNPs) are prepared by sonication‐mediated etching and redeposition (SMER) method and alkali‐earth‐metal hydroxide solution treatment. The HNPs are investigated to facilitate synergetic neuronal differentiation through alkali‐earth‐metal doping and in conjunction with nerve growth factor (NGF). PC12 cells are used as model cells for neuronal differentiation. The differentiation efficiency is improved in the presence of the HNPs+NGF, and the neurite length is in the order of Sr‐HNP+NGF > Ba‐HNP+NGF > p‐HNP+NGF > NGF. Silica/titania have increasing effect on both differentiation efficiency and neurite length, and doped barium/strontium influences additional elongation of the average neurite length. Take advantage of hollow structure, NGF is encapsulated into HNPs, and they are further applied for directly inducing differentiation. The maximum differentiation efficiency is 67% in presence of the NGF‐encapsulated Sr‐HNP, which was 1.3 times higher than previous research. Furthermore, the neurite length is also 2.7 times higher than MnO2 decorated poly(3, 4‐ethylenedioxythiophene) nanoellipsoids. Ba‐ and Sr‐HNP may offer a possibility for novel application of metal‐hybrid nanomaterials for cell differentiation, and can be expanded to other cellular applications.